Law Enforcement Problems and Impacts of the Law Development in Indonesia - Hamzani, Achmad Irwan (International Journal of Psychosocial Rehabilitation, 2020)
One of the crucial law issues in Indonesia is law enforcement. Law enforcement has received much attention, not only domestically, but internationally. Problematic law enforcement will have an impact on law development. The purpose of this study is to describe law enforcement in Indonesia, the factors that influence law enforcement in Indonesia, and the impact of law enforcement on national law development. This research uses a normative approach. The results showed that law enforcement is one element of the operation of the law. Without law enforcement, the purpose and function of law will not be fulfilled. If law enforcement has a problem, the purpose and function of the law will not be achieved. Law enforcement is strongly influenced by the mentality and morality of law enforcement. Culture of law-abiding society also affects law enforcement. The problem of law enforcement has an impact on the development of national law. Public pessimism about law enforcement has led to a loss of trust in the law.